Expeditious synthesis of aromatic-free piperidinium-functionalized polyethylene as alkaline anion exchange membranes. Issue 11 (1st February 2021) - You, Wei; Ganley, Jacob M.; Ernst, Brian G.; Peltier, Cheyenne R.; Ko, Hsin-Yu; DiStasio, Robert A.; Knowles, Robert R.; Coates, Geoffrey W.
Abstract : Piperidinium-functionalized polyethylene-based alkaline anion exchange membranes that show high hydroxide conductivities and good alkaline stabilities are easily prepared using photocatalytic hydroamination reactions. Abstract : Alkaline anion exchange membranes (AAEMs) with high hydroxide conductivity and good alkaline stability are essential for the development of anion exchange membrane fuel cells to generate clean energy by converting renewable fuels to electricity. Polyethylene-based AAEMs with excellent properties can be prepared via sequential ring-opening metathesis polymerization (ROMP) and hydrogenation of cyclooctene derivatives. However, one of the major limitations of this approach is the complicated multi-step synthesis of functionalized cyclooctene monomers. Herein, we report that piperidinium-functionalized cyclooctene monomers can be easily prepared via the photocatalytic hydroamination of cyclooctadiene with piperidine in a one-pot, two-step process to produce high-performance AAEMs. Possible alkaline-degradation pathways of the resultant polymers were analyzed using spectroscopic analysis and dispersion-inclusive hybrid density functional theory (DFT) calculations. Quite interestingly, our theoretical calculations indicate that local backbone morphology—which can potentially change the Hofmann elimination reaction rate constant by more than four orders of magnitude—is another important consideration in the rational design of stable high-performance AAEMs.